TINGKAT IMPLEMENTASI DAN HAMBATAN ADOPSI BUILDING INFORMATION MODELING PADA PELAKU PROYEK KONSTRUKSI DI BALI - Megapathi, I Made Agoes; Putera, I Gusti Agung Adnyana; Jaya, Nyoman Martha (JURNAL SPEKTRAN, 2021)
Many countries have established implementation strategies for the use of BIM in construction projects which have resulted in the widespread adoption of BIM. To catch up, the Ministry of PUPR has launched the Indonesia Digital Construction Roadmap 2017-2024 through 4 stages, namely the Adoption, Digitalization, Collaboration, and Integration stages. However, currently at the Adoption stage of the Roadmap, it is still focused on only a few PUPR infrastructure projects. This is due to problems such as the unavailability of policies and regulations for implementing BIM for the entire PUPR infrastructure sector, the lack of mastery of BIM from both Users and Service Providers, the project scale is not yet massive so that the price of BIM software is felt to be still burdening the Provider. This study aims to investigate the mastery of BIM through a study of the level of use, implementation, and identification of the dominant barriers to BIM adoption, especially for construction project actors in Bali. This research is expected to help construction industry practitioners to understand the challenges of BIM adoption in Bali. Data collection was carried out by survey method using a questionnaire. Respondents were selected using the purposive sampling method, namely experts in construction projects in Bali. The method of analysis is descriptive statistics which includes central tendency measurement, variability measurement, and the Relative Importance Index (RII). The survey results from all respondents showed that the adoption rate of BIM for construction project actors in Bali was 19%. Level of BIM implementation of construction project actors in Bali were 89% at BIM level 1 and 11% were at BIM level 2. The dominant obstacles in BIM adoption are the high cost of adoption, lack of experts, lack of government role in encouraging BIM adoption, difficulty changing work processes and there is no standard and protocol in applying BIM in the project.